Source-Specific Patterns of Marine Debris and Associated Ecological Impacts in the Red River Estuary of Xuan Thuy National Park, Vietnam - Giles, Rachel K.; Nguyen, Cindy Anh Thu; Hồ, Thu Thi Yến; Nguyến, Công Văn; Ngô, Ngoc Thi; Rochman, Chelsea M. (Frontiers in Environmental Science, 2021)
Anthropogenic marine debris is a ubiquitous contaminant found in remote ecosystems worldwide. Because rivers are a dominant source of marine debris, we aimed to understand the sources, accumulation patterns, and ecological effects of debris in the Red River (Song Hong) estuary. To assess debris patterns, we conducted standing stock debris surveys at sites in the mouth, and upstream of the Red River. To assess the ecological effects of anthropogenic debris on mangrove ecosystems, we measured mangrove diameter, canopy cover, and number of crab burrows m-2 in the same debris transects. Anthropogenic debris was found at all sites, and plastic was the most common material. We identified a non-significant trend, whereby ecological indices declined with increasing amounts of debris. Overall, our results demonstrate that anthropogenic debris is ubiquitous in the Red River estuary, composition varies among sites, and this debris may have adverse or neutral ecological effects on mangrove ecosystem health.